2016
DOI: 10.4067/s0718-58392016000300007
|View full text |Cite
|
Sign up to set email alerts
|

Studies of phenotypic and genotypic variation in sixteen cucumber genotypes

Abstract: Genetic variability in a crop population is important for successful plant breeding. Sixteen cucumber (Cucumis sativus L.) genotypes were evaluated in the early and late planting seasons to estimate the magnitude of their genetic variability and heritability. Genotypes were also classified into groups based on the performance and determination of the highest discriminating trait that accounted for greater variability using cluster analysis and principal component analysis (PCA), respectively. The measured agro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 11 publications
9
37
0
Order By: Relevance
“…Therefore indicating a predominance of additive gene effects and the possibilities of effective selection can be conducted based on these traits for crop improvement program. Similar findings were reported in Snap melon by Joseph (2012), Muddarsu and Venkat (2013), in cucumber by Ene et al, (2016), in Melon by Malik (2012), in Muskmelon by Tomar et al (2008) and in Watermelon by Thus these characters offer the best possibility of improvement through selection procedures.…”
Section: Resultssupporting
confidence: 80%
“…Therefore indicating a predominance of additive gene effects and the possibilities of effective selection can be conducted based on these traits for crop improvement program. Similar findings were reported in Snap melon by Joseph (2012), Muddarsu and Venkat (2013), in cucumber by Ene et al, (2016), in Melon by Malik (2012), in Muskmelon by Tomar et al (2008) and in Watermelon by Thus these characters offer the best possibility of improvement through selection procedures.…”
Section: Resultssupporting
confidence: 80%
“…In this regard, Esho and Saeed (2016) and Hassan et al (2016) indicated that the variability among summer squash varieties attributed to its genetic make-up. The varietal differences in this connection were also reported by Aly (2002) and Yoldas (2014) who working on summer squash, and Ene et al (2016) on cucumber. They demonstrated that fruit physical characters were significantly affected by the variety.…”
Section: Fruit Quality 1 Fruit Physical Characters a Effect Of Cultsupporting
confidence: 72%
“…These results are in accordance with those obtained by Aly (2002), Yoldas (2014) and Hassan et al (2016) on summer squash, who recorded a significant difference between the tested hybrid squash cultivars and Eskandarany cv., in yield and its components. In this connection, Marie et al(2011), Saeed (2016 and, as well as Kumar and Sharma (2018) all working on different varieties and hybrids of squash, and Ene et al (2016) on cucumber , reported that the differences between either squash or cucumber varieties in number of fruits per plant and total yield attributed to the genetic variation. However, Bielinski et al (2008) stated that members of cucurbits plants are adapted to particular dominant of temperature which considered a main factor influencing of flowering, the opening of flowers, as well as growth of fruits which reflected on yield.…”
Section: Yield and Its Components A Effect Of Cultivarsmentioning
confidence: 99%
“…Whereas, YI, YSI and DRI had low genetic advance along with high heritability indicated that the effects of environments are greater more than the effects of genetics. Because of the three indices will not useful for further selection (Ene et al, 2016 andBesufikad, 2019).…”
Section: Broad Sense Heritability and Genetic Advancementioning
confidence: 99%
“…Genotypic coefficient of variance supplies facts on the genetic variation display in quantitative traits in base population, but it is too difficult to define the quantity which was heritage. So the heritability measurements assist it to predict the improvement in the selection (Ene et al, 2016). Thus, the heritable portion of the variation could be more useful with help of heritability estimates.…”
mentioning
confidence: 99%